“The victim lived an intense life”: media (mis)representations of femicide crimes in the Republic of Cyprus - Papa, Venetia; Kouros, Theodoros; Lambe, Andrea (My University, 2024)
International media research has recently emphasized the coverage of “partner homicides” in news media outlets with specific focus on the traits/characteristics and the forms of femicides. This led us to consider the ways in which news media outlets construct, portray, affect audiences and certain groups of individuals through the representations of such crimes. Through thematic content analysis of crime news, the purpose of this study is to determine how femicide victims are portrayed by major news media outlets in the Republic of Cyprus. The research consisted of an analysis of 366 femicide-related articles referring to 37 femicides that took place from 2006 to 2020. The data were analyzed to determine effects on newsworthiness, public perception, and patterns of victim blaming. The phenomenon of victim blaming emerged from the analysis as a recurring frame, both in a direct and indirect manner. Such blaming strategies include the usage of language with negative connotations in descriptions of the victim, such as highlighting their “promiscuous” pasts, and the attribution of “male honor”-related motives to the perpetrators, using sympathetic language to describe the perpetrator, highlighting the victim’s mental or physical problems, and so forth.
Keywords: Cyprus; Femicide; gender; media; victim-blame